Small molecules fail to induce direct reprogramming of adult rat olfactory ensheathing glia to mature neurons - Portela-Lomba, María; Simón, Diana; Fernández de Sevilla, David; Moreno-Flores, Mª Teresa; Sierra, Javier (Frontiers in Molecular Neuroscience, 2023)
An approach to generate new neurons after central nervous system injury or disease is direct reprogramming of the individual´s own somatic cells into differentiated neurons. This can be achieved either by transduction of viral vectors that express neurogenic transcription factors and/or through induction with small molecules, avoiding introducing foreign genetic material in target cells. In this work, we propose olfactory ensheathing glia (OEG) as a candidate for direct reprogramming to neurons with small molecules due to its well characterized neuro-regenerative capacity. After screening different combinations of small molecules in different culture conditions, only partial reprogramming was achieved: induced cells expressed neuronal markers but lacked the ability of firing action potentials. Our work demonstrates that direct conversion of adult olfactory ensheathing glia to mature, functional neurons cannot be induced only with pharmacological tools.